Application of bacterial cellulose in dietary fiber-enriched castella cake production. Issue 1 (31st December 2023) - Vo, Tan Phat; Tran, Hoang Khanh Linh; Pham, Nhat Tien; Tran, Tri Nguyen; Nguyen, Thuy Hong Nhung; Phan, Thuy Han; Lee, Hyunjoo; Nguyen, Dinh Quan
ABSTRACT: In this study, bacterial cellulose (BC) was used as a partial replacement for baking wheat flour in the traditional castella cake recipe to increase the fiber content. The wheat flour content was partially replaced (5, 10, 15, and 20%) with BC powder (BCP) in the castella cake recipe, while 0% replacement was used as the control sample. The fiber-enriched castella cake's physical texture, chemical composition, and sensory properties were analyzed. With up to 20% incorporated BC, the castella cakes had their density and total dietary fiber content increased by 1.72 and 3.57 times, respectively, compared to the control samples. Among the samples, the sensory evaluation showed that the 5 and 10% BC replaced fiber-enriched castella cakes were favored by consumers. The total dietary fiber content of 10% BC replaced fiber-enriched castella cake was 5.83 ± 0.31%db; thus, this ratio was recommended in a castella cake recipe. uf0001